Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation, Mediation, and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation, Industrial; Officials and employees; Social justice

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration

The contribution mediation can make in addressing economic crime in corporate and commercial relationships in South Africa - Hoffman, Cornelia Hendrina (Stellenbosch University, 2019)
Economic crime is complex and costly. It is costly because it harms victims, both directly and indirectly, as well as the broader economy. The cost is not only financial, but also to confidence and trust in corporate and commercial relationships in South Africa. Economic crime is complex because it includes offences from common-law fraud to statutory contraventions such as incorrect bookkeeping. There are several mechanisms in the South African legal justice system to address economic crime. The conventional legal models include adversarial criminal prosecution of the offender and civil compensation claims, the model of inquisitorial administrative investigations and sanctions like penalties and compensation orders. In 2001 section 105A of the Criminal Procedure Act, namely plea and sentencing agreements, was added as a model of negotiated justice. This mechanism allows the prosecution and the offender to negotiate and enter into an agreement regarding the charges and the sanctions, subject to approval of the court that the plea of guilty is proper and that the proposed sanction is a just sentence. This dissertation proposes that mediation be added to the existing alternative models to help combat economic crime. Mediation involves negotiated justice, as well as restorative justice. More specifically, mediation as a restorative justice process, constitutes a practical alternative to standard litigation as the affected parties themselves, with the facilitation of a third person, resolve the disputes between them. Mediation, a facilitative and flexible procedure, allows the voices of both the victim and the offender to be heard securely and meaningfully. Mediation is rehabilitative and allows for agreed restorative provisions for both the perpetrator and the victims of economic crime. The outcome is a proposed amendment to the Criminal Procedure Act 51 of 1977, namely the insertion of section 105B, “Mediated Settlement Agreements”, that will provide for mediation and a mediated settlement agreement to be incorporated into and form part of the criminal justice processes. It is envisaged that an accredited mediator will mediate between the parties, including the public prosecutor, the perpetrator, the victim and possibly members of the community. The mediated settlement agreement will include both compensation for the victims and a proposed sentence for the perpetrator. This mediated settlement agreement will then be tabled before the court for adjudication and approval to serve as an effective court order. The proposal is a logical legal development of section 105A of the Criminal Procedure Act on plea and sentencing agreements, as the process of mediation builds on the process of negotiation established in it. To put it bluntly, if a plea and sentence agreement can be negotiated between the prosecutor and the offender, a plea and sentence agreement can be mediated between the prosecutor, the offender and the victim. Mediation can integrate and expand the constitutional principles of reparation and ubuntu and curb economic crime by providing an effective restorative and just response to it.
Keywords: Alternatives to prosecution; Commercial law; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; South Africa

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

International Standards for Commercial Mediators - To, Christopher (University of Stirling, 2015)
This paper talks about the international standards for commercial mediators. It introduces the standards of eight different jurisdictions and afterwards, evaluates whether there should be one accrediting standard for all international commercial mediators. In the introduction chapter, the paper talks about the problems with the current legal system and then explains the growth of mediation in today’s society. By discussing the nature and practice of mediation, whether mediation should be compulsory or voluntary in light of Article 6 of the European Convention on Human Rights, rationale of the various jurisdictions covered, the paper then talks about the attributes that make a good mediator as well as the accreditation and training of mediators. From chapter two to chapter nine, the paper focuses on eight jurisdictions in which mediation is firmly enshrined within one legal culture to those that are just embarking on the concept (namely Australia, New Zealand, Indonesia, Malaysia, India, Hong Kong, California and Canada). Each chapter talks about the developments of commercial mediation, law and institutions as well as training and accreditation of mediators within their respective jurisdictions. In the concluding chapter, it discusses whether there should be one accrediting standard for international commercial mediators by exploring the advantages and disadvantages of having one accrediting standard as well as the author’s analysis and point of view on the subject.
Keywords: Commercial mediator; International standards; Mediation; Mediator; Médiateur

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

Economic and Empirical Analysis of Contractual Dispute Resolution - Miller, Samuel Mark (Vanderbilt University, 2015)
This dissertation uses Python-based programming to retrieve and analyze a sample of approximately 400,000 material contracts that companies filed with the Securities and Exchange Commission between 2001 and 2013, focusing on the dispute resolution mechanisms specified therein. The first chapter considers the effectiveness of two state-level efforts to attract dispute resolution business, examining how specialized “business courts” and the Revised Uniform Arbitration Act affected arbitration and choice-of-forum clause use in these material contracts. The second chapter examines whether and how companies and executives “customized” their arbitration clauses in response to Internal Revenue Code Section 409A, which increased both the likelihood and the complexity of potential disputes between these parties. The third chapter considers how companies and executives responded when the Supreme Court overturned the Ninth Circuit’s anomalous refusal to enforce employment-related arbitration clauses. Each chapter finds that contracting parties adjusted their dispute resolution provisions in response to the policy change(s) at issue – suggesting that for the sophisticated parties in my dataset, these provisions receive careful thought and are not mere “boilerplate.”
Keywords: Arbitrage; Arbitragem; Arbitration; Contracts; Dispute resolution; Econometrics

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

Arbitration in administrative contracts : comparative law perspective - Lin, Ching-Lang (Institut d'études politiques, 2014)
Il a été longuement discuté de savoir si le système d'arbitrage est applicable pour régler les litiges administratifs qui concernent certains contrats administratifs ou d’autres sans rapport avec le contrat administratif. Dans cette thèse, les trois questions spécifiques sont analysées tour à tour : (1) Est-il possible pour un arbitre ou un tribunal arbitral de trancher des questions relevant du droit administratif? (2) Y a-t-il, ou devrait-il y avoir, des limitations à l'autorité des arbitres et des tribunaux arbitraux? (3) Enfin, après la délivrance d'une sentence arbitrale, quel rôle devrait jouer l'État dans la phase de contrôle judiciaire? La première question concerne l'arbitrabilité et a été discutée dans la première partie (FIRST PART: ARBITRABILITY). La deuxième question a été discutée dans la deuxième partie (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Enfin, sur la dernière question a fait l’objet d’une troisième partie (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). Dans cette thèse, nous avons comparé les systèmes de quatre pays (Canada, Chine, France, Taïwan). En conclusion, nous pouvons donc conclure que l’évolution de la conception du contrat administratif implique de nombreux aspects, y compris les aspects juridiques, économiques, politiques et même culturels. Le développement de la fonction de contentieux administratif, comme ‘’subjectivement orienté" ou "objectivement orienté" aura une incidence sur l'acceptation de l'arbitrage en matière administrative. Dans l'ensemble, l'arbitrage sera plus acceptable dans les systèmes dont la fonction est plus ‘’subjectivement orientée" que dans ceux dont la fonction est "objectivement orientée". While arbitration has traditionally been considered as a means to resolve private disputes, its role in disputes involving administrative contracts is a crucial question in administrative law. In brief, the three specific questions are (1) Can arbitrators or arbitral tribunals decide issues involving administrative law? and (2) Is there, or should there be, any limitation on the authority of arbitrators or arbitral tribunals? (3) Moreover, after the issue of an arbitration award, what role should the State play in the judicial review phase? The first question, the issue of arbitrability, is discussed in part 1 (FIRST PART: ARBITRABILITY). The second question will be discussed in part 2 (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Finally, on the question of what happens after the arbitration award, we will discuss judicial review in part 3 (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). We compare legal systems between the four countries: in France, in Canada, in China and in Taiwan. We believe that an administrative contract, at least in its function and conception, is gradually becoming different from a private contract. Innovation with respect to administrative contracts will also reflect the concentration and function of the administrative litigation systems in each country. In addition, the “objective” or “subjective” function of administrative litigation will also affect the degree of arbitrability, as well as arbitration procedures. Taken together, arbitration will be more acceptable in systems whose function is more “subjectively oriented” than in those whose function is “objectively oriented". Finally, “the arbitration of administrative matters” traditionally has been an important question in administrative and arbitration law. In the future, we will continue to see it shine in the doctrine and jurisprudence of both the administrative and arbitration law fields.
Keywords: Administrative litigation system; Arbitrability; Arbitrabilité; Arbitrage; Arbitragem; Arbitration; Arbitration award; Contentieux administratif; Contrats administratifs (exécution); Judicial review; Litige; Légalité objective; Objective and subjective function; Prerogative of administrations in contracts; Sentence arbitrale (contestation); Études comparatives

Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)

A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch University, 2013)
Arbitration as a mode of dispute settlement has been growing steadily all over the world. The momentum for commercial arbitration in particular was provided by the 1985 UNCITRAL Model Law on International Commercial Arbitration (“the Model Law”). Legislation based on the Model Law has been enacted in many countries. The arbitration laws of three of these countries, Kenya, Nigeria and Zimbabwe, are selected for consideration in this dissertation because of their common origins, similar statutes, similar problems, shared experiences, and their regional distribution. As the writer’s arbitration practice is based in Kenya, that jurisdiction is the primary, albeit not the only, source and foundation for this work, the focal point of reference and the citations from the law and practice incorporated in this research. The work consists of three chapters. Chapter one is a brief introduction and an overview of arbitration. This is followed by the statement of the research question, the justification for the research, methodology and the structure and content of the dissertation. Chapter two describes the legal and contextual framework for the investigation of the research questions in the selected jurisdictions of Kenya, Nigeria and Zimbabwe. Customary Law arbitration is included as a significant feature of African arbitration law. The UNCITRAL Model Law, the Arbitration Act, 1995 (Kenya), the Arbitration and Conciliation Act, 1988 (Nigeria), the Arbitration Act, 1996 (Zimbabwe), the Arbitration Act, 1996 (England), and the South African Draft Arbitration Bill are all used as legislative or statutory points of reference in the discussion of the research questions. Chapter 3 contains the main focus of the dissertation in which six recurrent arbitration problems in Kenya are discussed in the context of domestic arbitration. The research investigates (i) the illusiveness of consent as the basis for consensual arbitration (ii) jurisdictional challenges (iii) the procedural powers of the arbitral tribunal (iv) the disruptive effect of adjournments and postponements on the arbitral process (v) constraints on the granting of interim relief and (vi) the enforcement of the arbitral award. Original, creative and innovative proposals in response to these problems include: the express legislative recognition of the manifestation of consent in both the verbal and written forms of the arbitration agreement, the use of the constructive dispute resolution technique, statutory recognition of customary law arbitration, the use of an expedited arbitration procedure, the award of exemplary and punitive damages in arbitration, a code of sanctions to facilitate the arbitration process, and a simplified method of enforcement and execution of the arbitral award. The dissertation concludes with reflections on the future of arbitration in Africa, and the need for modernization and harmonization of arbitration laws for peaceful resolution of disputes and serious conflicts across Africa. The aim of this study is best illustrated by a short story: In the early nineties there was a man, untrained in any known discipline, who strutted court corridors, trade centres and market places, carrying a placard advertising himself to lawyers, traders and marketers as “An Arbitrator and Private Judge”. He attracted business, charged a handsome percentage fee on the value of the claim, was duly paid, until officialdom caught up with him and put paid to his burgeoning career as “Arbitrator-Judge”. But the reckless enthusiasm spawned by his wit and imagination, and the idiosyncratic practices in dispute resolution persisted and are manifest in Kenyan arbitration culture today. The need to remove bad practices, avoidable impediments, and inefficiency in the arbitration culture of Kenya in order to make its procedures and processes more efficacious, is the heart of this study.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Comparative law; Dispute resolution; Kenya; Nigeria; Zimbabwe

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Essays on Bargaining with Outside Options - Adamuz Peña, Mercedes (Universitat Autònoma de Barcelona, 2002)
Los modelos de negociación con opciones exteriores normalmente suponen que los pagos de estas opciones son independientes de las acciones que los negociadores toman durante el proceso negociador. Sin embargo, en muchos contextos, la opción exterior depende de lo que las partes hagan durante la fase negociadora. Uno de estos contextos es el de aquellas negociaciones que se llevan a cabo en presencia de un árbitro. Esta tesis realiza algunas contribuciones a la teoría de la negociación con opciones exteriores, enfatizando aquellas situaciones donde las opciones exteriores aparecen por la intervención de árbitros. En el capítulo 2 analizo los efectos del arbitraje en las negociaciones cuando su uso es voluntario. Considero un modelo de negociación por concesiones donde las partes tienen la posibilidad de llamar a un árbitro con el consentimiento del oponente. Demuestro que la introducción del arbitraje distorsiona el resultado de la negociación. Esta distorsión depende de los costes relativos de implementar una partición mediante un proceso negociador versus un proceso arbitral. Si los costes del arbitraje son pequeños en relación a los costes de la negociación, entonces la partición negociada se aproxima a la propuesta por el árbitro, y en casos extremos el arbitraje es utilizado en equilibrio. Sin embargo, los jugadores no eligen siempre el método más eficiente de resolver su disputa: a veces negocian cuando es más eficiente acudir al arbitraje. En el capítulo 3 estudio los efectos de diferentes procedimientos arbitrales en el resultado de una negociación, en un modelo donde los jugadores realizan demandas no crecientes y el árbitro es llamado solo cuando las negociaciones se declaran rotas. Dos procedimientos arbitrales son analizados: el arbitraje convencional, donde el árbitro es libre de elegir su acuerdo y el arbitraje de oferta final, donde el árbitro está obligado a elegir una de las últimas ofertas de los jugadores. Demuestro que si los jugadores son suficientemente pacientes y el árbitro sigue un procedimiento de oferta final, en equilibrio, los jugadores negocian una partición pero toma algún tiempo llegar a ella. Sin embargo, si el árbitro sigue un procedimiento convencional, en equilibrio los jugadores utilizarán esta institución para resolver su disputa. Finalmente, en el capítulo 4 discuto el papel que juegan las opciones exteriores inciertas en las negociaciones cuando existe información incompleta acerca de su existencia. Examino una guerra de desgaste donde los jugadores disfrutan de información privada acerca de sus posibilidades de dejar la mesa de negociación para tomar una opción exterior. Hay dos tipos de jugadores: los tipos débiles, que no tienen opciones exteriores y prefieren conceder que salirse del juego, y los tipos fuertes que tienen opciones exteriores tales que prefieren salirse que conceder. El principal mensaje que surge del análisis de este juego es que la incertidumbre acerca de la posibilidad de que el oponente se vaya, mejora la eficiencia porque incrementa la probabilidad de concesión. Más precisamente, si la probabilidad de que el oponente sea fuerte es relativamente alta, la negociación acaba con una concesión segura. En el otro extremo, si la probabilidad de que el oponente sea débil es alta, los tipos fuertes dejarán en algún momento el juego con probabilidad igual a 1, dejando a los débiles jugando, desde ese momente en adelante el ineficiente equilibrio de la guerra de desgaste clásica. Incluso en este caso, la probabilidad de concesión a lo largo de la fase de incertidumbre del juego se incrementa.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ciències Socials; Conventional arbitration; Final-offer arbitration; Negociación; Opciones exteriores

Procedural detachment in international commercial arbitration : the law applicable to arbitral procedure - Petrochilos, Georgios (University of Oxford, 2000)
This thesis seeks to ascertain the rules of private international law determining the procedural law of international commercial arbitral proceedings. In an Introduction, the author outlines the fundamental notions, introduces the topic and the major doctrines and issues, and sets out his methodology and structure of the work. The thesis examine first, as a preliminary issue, the considerations influencing the assumption of jurisdiction over arbitral proceedings. Chapter 1 discusses the various theories on the lex arbitri (the law supplying the general legal framework of an arbitration) as relevant to the procedural law, and concludes that they are deductive and therefore unable to satisfactorily to determine the applicable procedural law. Chapter 2 analyses major national laws as case-studies of the technique and scope of application of international arbitration law, and suggests a model of legislative and court jurisdiction based on the legal concept of 'seat of the arbitration' and on considerations based on the most appropriate court to control an arbitration. Chapter 3 discusses the obligations of the state of the seat under the European Convention on Human Rights and confirms the findings in Chapter 2. In a second part, the thesis elaborates on the title and extent of permissible municipal law interference. Chapter 4 tests the validity of the propositions derived from Chapters 2 and 3 against arbitral practice and concludes that seldom will arbitrators derogate from the law of the seat. Chapter 5 examines the particular case of arbitrations with states and similar entities. The third part discusses the relevance of compliance with the law of the seat at the stage of enforcement of an award. Chapter 6 deals with the technical issue of whether annulment at the place of making precludes enforcement in other fora. That chapter gives the opportunity to discuss models of separation of international jurisdiction and co-operation between different jurisdictions from a practical perspective. It thus serves as a convenient introduction to Chapter 7, which discusses the more abstract question of the nexus required between an arbitral award and the municipal law of the state of rendition in order for the award to enter, in limine, the scope of application of the international instruments in the field. The thesis ends with Conclusions in the form of model provisions for municipal law and arbitration rules.
Keywords: Arbitrage; Arbitragem; Arbitration; International commercial arbitration; Procédure arbitrale

Improving the administration of justice through the implementation of third party alternative dispute resolution processes: An analysis of process productivity and disputant strategic behavior - Stanford, John D. (Ohio State University, 1996)
The institutionalization of alternative dispute resolution (ADR) processes is the most recent development in the policy effort to reform the American civil justice system. However, the research is inconclusive and contradictory on the performance of ADR processes in institutionalized settings. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study concludes that the court annexed arbitration is the best performing process. Of the various dispute, disputant, and process characteristics identified to explain process perform ance, only the disputant’s perception of process equity during the process is significant and positive. The policy inference is that policy makers can reduce disputant costs while improving delay, process equity, and satisfaction through court-annexed arbitration.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Third party